Gene expression analysis of stem cell from exfoliated deciduous teeth in migration and local angiogenesis of tissue repair - Aziz, Nur Syazwani (2020)
Stem cells play essential role during the angiogenesis process of wound healing. Stem cells from exfoliated deciduous teeth (SHED) possess mesenchymal stem cell (MSC) characteristics, showing the ability to differentiate into various lineages, indicating their massive potential to benefit cell-based therapy and tissue repair. Nevertheless, the behaviour of SHED engaging in angiogenesis in terms of its migratory capacity and gene expression regulation remains questionable. The present study aims to analyse the gene expression pattern of SHED undergoing migration and angiogenic differentiation. Together, the effect of different initial seeding density and induction medium on the migration of SHED were assessed. SHED were expanded in vitro and induced for angiogenesis by supplementation of 10 ng/ml of vascular endothelial growth factor (VEGF) in 2 ml of endothelial growth medium 2 (EGM2). Scratch test assay was conducted in the transwell chamber to determine the optimum initial seeding density for SHED by comparing 5,000 cells/cm2 and 10,000 cells/cm2 prior to angiogenic induction. A further comparison was made to assess the effect of angiogenic induction media on SHED migration rate. Three groups of SHED were assessed the gene expression analysis: the angiogenic induction group (+A-M), angiogenic induction with migration group (+A+M), and the control group (-A-M). RNA was extracted at different time points (day 1, 3, 7, 10 and 14). One-step RT-PCR was then performed to assess the gene expression level of a series of angiogenic, migration and MSC gene markers. Overall, the data demonstrated a high capability of SHED committing to angiogenic lineage. Higher seeding density (10,000 cells/cm2) increased SHED migration, whereas angiogenic induction suppressed SHED migratory capacity. SHED positively expressed Ang-1, Il-8, and VE-Cadherin, the angiogenic markers, as well as the migratory gene markers (CCR1, CXCR4 and CCL28). SHED also maintains the stemness level by positive expression of CD73, CD90 and CD105 during the induction protocol. The gene expression pattern of both angiogenic and migratory gene markers observed within this study indicate the complexity of understanding these two events during tissue repair. Indeed, a better understanding of these SHED-chemokine interactions is needed to enable the effective use of SHED in cell-based therapies.